A DNA-engineered metal–organic-framework nanocarrier as a general platform for activatable photodynamic cancer cell ablation. Issue 2 (4th January 2023) - Ma, Yahui; Chen, Renzeng; Chen, Xianheng; Sun, Yuqi; Wang, Yuanbo; Wang, Bo
Abstract : A DNA-engineered metal–organic-framework nanocarrier is proven to be a general platform for both hydrophobic and hydrophilic photosensitizers to realize activatable photodynamic cancer cell ablation. Abstract : Activatable photodynamic cancer cell ablation constitutes a promising approach to performing highly effective photodynamic therapy (PDT) with mitigated phototoxicity. Regretfully, so far strategies to fabricate activatable PDT agents are only applicable to a limited number of photosensitizers (PSs). Herein, an activatable photodynamic cancer cell ablation platform that can be adopted for versatile PSs is presented. Thereinto, by engineering an iron(iii ) carboxylate-based metal–organic framework (MOF), MIL-101(Fe), with DNA grafted after PS loading, both hydrophilic and hydrophobic PSs can undergo negligible unspecific leakage and significant suppression of photosensitization during delivery. Following the reaction between MIL-101 and H2 O2 whose level is greatly increased inside the tumor, MIL-101 is selectively degraded to release the loaded PDT agents and recover their photosensitization, controllably killing cancer cells upon H2 O2 activation. Such a strategy assisted by a DNA-functionalized MOF significantly expands the varieties of PSs applicable for activatable PDT.